Shocks, frictions, and business cycles in a developing Sub-Saharan African economy - Noah Ndela Ntsama, Jean Frederic (2011)
This thesis examines the sources of business cycle fluctuations in a developing Sub-Saharan African economy. We develop an open economy dynamic stochastic general equilibrium model (DSGE), which is log-linearized, calibrated, and estimated with Bayesian techniques using South Africa macroeconomic data. The model incorporates various features such as external habit formation, internal investment adjustment cost, variable capacity utilization, domestically produced goods prices and wages stickiness, incomplete exchange rate pass-through, and financial accelerator. The DSGE model also integrates seven orthogonal structural shocks: a financial market shock that affects both the premium on the assets held by households and the foreign interest rate, a cost-push shock, a productivity shock in the domestically produced goods sector, an export demand shock, a terms of trade shock, a government spending shock, and a monetary policy shock. The introduction of those structural shocks allows for an empirical investigation of their effects and contributions to business cycle fluctuations in the South African economy. Simulating the DSGE model and decomposing the forecast error variances of the observable macroeconomic variables, it emerges that the main driving forces of the growth rates of real GDP, consumption, and investment, as well as the trade balance to GDP ratio, are the export demand shock, the government spending shock, the terms of trade shock, and the productivity shock. The productivity, the price mark-up, and the terms of trade shocks drive the aggregate inflation. The financial market shock predominantly impels the domestic interest rate, while the monetary policy shock largely causes the exchange rate fluctuations. Real, nominal, and financial frictions are necessary to capture the dynamic of the South Africa macroeconomic data and critical to explain their volatility and persistence.